Perovskite solar mini-modules - Bruno, Annalisa (2022)
In the last decade perovskite solar cells have shown remarkable improvements in power conversion efficiency which have driven the interest to commercialise the perovskite technology. Here, I will present an overview of our recent works focused on the development and the understanding of highly efficient co-evaporated perovskite solar cells with excellent thermal stability and remarkable upscalability. Our works demonstrate the compatibility of perovskite technology with consolidated industrial processes and its potential for next-generation photovoltaics on the market.